Composite Hydrogels in Three-Dimensional in vitro Models - Zhao, Zhitong; Vizetto-Duarte, Catarina; Moay, Zi Kuang; Setyawati, Magdiel Inggrid; Rakshit, Moumita; Kathawala, Mustafa Hussain; Ng, Kee Woei (Frontiers in Bioengineering and Biotechnology, 2020)
3-dimensional (3D) in vitro models were developed in order to mimic the complexity of real organ/tissue in a dish. They offer new possibilities to model biological processes in more physiologically relevant ways which can be applied to a myriad of applications including drug development, toxicity screening and regenerative medicine. Hydrogels are the most relevant tissue-like matrices to support the development of 3D in vitro models since they are in many ways akin to the native extracellular matrix (ECM). For the purpose of further improving matrix relevance or to impart specific functionalities, composite hydrogels have attracted increasing attention. These could incorporate drugs to control cell fates, additional ECM elements to improve mechanical properties, biomolecules to improve biological activities or any combinations of the above. In this Review, recent developments in using composite hydrogels laden with cells as biomimetic tissue- or organ-like constructs, and as matrices for multi-cell type organoid cultures are highlighted. The latest composite hydrogel systems that contain nanomaterials, biological factors, and combinations of biopolymers (e.g., proteins and polysaccharide), such as Interpenetrating Networks (IPNs) and Soft Network Composites (SNCs) are also presented. While promising, challenges remain. These will be discussed in light of future perspectives toward encompassing diverse composite hydrogel platforms for an improved organ environment in vitro.